A 64‐channel 3T array coil for accelerated brain MRI. Issue 1 (31st July 2012) - Keil, Boris; Blau, James N.; Biber, Stephan; Hoecht, Philipp; Tountcheva, Veneta; Setsompop, Kawin; Triantafyllou, Christina; Wald, Lawrence L.
Abstract A 64‐channel brain array coil was developed and compared to a 32‐channel array constructed with the same coil former geometry to precisely isolate the benefit of the 2‐fold increase in array coil elements. The constructed coils were developed for a standard clinical 3T MRI scanner and used a contoured head‐shaped curved former around the occipital pole and tapered in at the neck to both improve sensitivity and patient comfort. Additionally, the design is a compact, split‐former design intended for robust daily use. Signal‐to‐noise ratio and noise amplification (G‐factor) for parallel imaging were quantitatively evaluated in human imaging and compared to a size and shape‐matched 32‐channel array coil. For unaccelerated imaging, the 64‐channel array provided similar signal‐to‐noise ratio in the brain center to the 32‐channel array and 1.3‐fold more signal‐to‐noise ratio in the brain cortex. Reduced noise amplification during highly parallel imaging of the 64‐channel array provided the ability to accelerate at approximately one unit higher at a given noise amplification compared to the sized‐matched 32‐channel array. For example, with a 4‐fold acceleration rate, the central brain and cortical signal‐to‐noise ratio of the 64‐channel array was 1.2‐ and 1.4‐fold higher, respectively, compared to the 32‐channel array. The characteristics of the coil are demonstrated in accelerated brain imaging. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.